Taxprayer Rights in Cancellation Of Tax Assessment Letter - Yudha Pangesti, Wahyu Sandhya; Yuhelson , Yuhelson; Suasungnern, Sineerat (Journal Evidence Of Law, 2025)
This research focuses on the rights of taxpayers in the cancellation of Tax Assessment Letter (SKP). In Indonesia, taxpayers have the right to apply for cancellation of an SKP that is deemed erroneous. However, some rights such as access to information, the right to clarity of process, and the right to object are often hampered by complex administrative mechanisms. This research aims to identify taxpayers' rights in the context of SKP cancellation and evaluate whether these rights are adequately fulfilled. The results show that there is a gap between regulation and implementation, making it difficult for taxpayers to obtain their rights effectively.